The Portrayal of Affection on The Weekend’s Die For You - Pasopati, Rommel Utungga; Pujimahanani, Cahyaningsih; Maulidia, Maulidia; Zhafirah, Muthiah Qalbu; Farashifah, Na’ilah (PARAFRASE : Jurnal Kajian Kebahasaan & Kesastraan, 2025)
The song Die for You tells the story of someone who loves the couple then comes to a point where he wants to leave his couple but he thinks that his lover is too perfect to be left behind. By using qualitative method, this paper answers the question of how is the idea of affection portrayed in the song Die for You by The Weeknd?. Die for You portrays the idea of love through its lyrics that express devotion and loyalty to a lover. It proves that affection is about possibility as supported by Affection Exchange Theory by Kory Floyd. The possibility is about showing affection more than merely words, but through real efforts and actions. It is a process that emphasizes love to be applied furthermore with rational thinking. Moreover, this paper also finds its significance to study how affection works in contemporary popular culture. In conclusion, the song accentuates matter of affection as a background of thinking of reasoned love. It is never given at all, but always be interpreted through various reasoned senses.